Emerging role of local and extended range molecular structures on functionalities of topological phases of (Na2O)x(P2O5)100‐x glasses using Raman scattering and modulated DSC. (29th July 2020) - Mandal, Avik; Gogi, Vamshi Kiran; Mohanty, Chandi; Chbeir, Ralph; Boolchand, Punit
Abstract: Raman scattering is a powerful probe of local structure (LS) of glasses. In Sodium Phosphate Glasses (SPGs), we show that both LS composed of Q n species and Extended Range Structures (ERS) composed of Long Chains (LCs), Large Rings (LRs), and Small Rings (SRs) can be decoded by Raman scattering. The trimodal distribution of P‐Oterminal stretch modes of Q 2 species and P‐Obridging at x  < 50% are manifestations of these ERS . These two pairs of triads of modes are uniquely identified with Q 2 units present in either LCs, or LRs, or SRs. The existence three phases of c‐NaPO3 composed of 3‐membered rings, 6‐membered rings, and infinitely long chains has facilitated the identification. The Intermediate Phase (IP) in SPGs extends in the 37.5 <  x  < 46.0% range, the Stressed‐rigid Phase in the 46.0% <  x  < 50%, and the Flexible Phase in the 18% <  x  < 37.5% range of soda. We show the IP consists predominantly of LCs (82%), with a minority of LRs (15%) and SRs (3%). The LR‐ and SR‐fractions increase measurably in the non‐IP phases. The structural finding is in harmony with the high configurational entropy of the IP glasses that leads aging to be qualitatively suppressed.